2003
DOI: 10.2134/agronj2003.4960
|View full text |Cite
|
Sign up to set email alerts
|

Soil Electrical Conductivity Map Variability in Limestone Soils Overlain by Loess

Abstract: Sensors exist that allow rapid mapping of bulk soil electrical confurther research. Variation in bulk soil EC may occur ductivity (EC); however, the utility of these sensors for Kentucky producers is unknown. The purpose of this study was to assess the at spatial and temporal scales including the microscale nature and the causes of soil EC variability and to make a first assess-(variation in EC at distances or times less than the ment of its potential utility in Kentucky, particularly for fields consampling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 25 publications
3
45
1
6
Order By: Relevance
“…They were large for slope because slope phase was an important factor for soil mapping and perhaps the most easily observed feature. The first-order OLS F-values for EC values were fairly sizable because studies have shown that important taxonomic factors vary with EC such as topsoil thickness, depth to fragipan, drainage and clay content (Doolittle et al, 1994;Kravchenko et al, 2002;Mueller et al, 2003). The F-values for plan and profile curvature and aspect DFN were relatively small, consistent with the poor relationships observed between these variables and first-order soil mapping units (e.g., Figure 3).…”
Section: Soil Ec and Terrain Attributes Interpretationssupporting
confidence: 54%
See 2 more Smart Citations
“…They were large for slope because slope phase was an important factor for soil mapping and perhaps the most easily observed feature. The first-order OLS F-values for EC values were fairly sizable because studies have shown that important taxonomic factors vary with EC such as topsoil thickness, depth to fragipan, drainage and clay content (Doolittle et al, 1994;Kravchenko et al, 2002;Mueller et al, 2003). The F-values for plan and profile curvature and aspect DFN were relatively small, consistent with the poor relationships observed between these variables and first-order soil mapping units (e.g., Figure 3).…”
Section: Soil Ec and Terrain Attributes Interpretationssupporting
confidence: 54%
“…In another Kentucky study, shallow EC increased as depth to the fragipan horizon surface decreased under dryer (r 2 ¼ 0.81) but not wetter (r 2 ¼ 0.11) conditions (Mueller et al, 2003). A similar relationship was not apparent in this (Table 4) potentially because the EC data for the Calloway County field were collected in March of 2001 when the soils were fairly wet.…”
Section: Soil Ec and Terrain Attributes Interpretationsmentioning
confidence: 81%
See 1 more Smart Citation
“…The contrasting effect of low temperature and high content of soil organic matter in the one replicate block was thus less important for the results. Mueller et al (2003) also suggested that other soil properties (e.g. soil particle size) masked the effect of soil temperature on EC a in their experiment.…”
Section: 'Noise' From Variable Soil Properties Other Than Cn Inorgmentioning
confidence: 89%
“…EM H , EM V , soil water content and temperature were considered as sensor variables, and the best model was sought. The measurements of EC a (EM H and EM V ) were both 'true' sensor variables, whereas soil water content and temperature were considered as hypothetical sensor variables, since 'on-the-go' measurements of these variables are feasible (Mueller et al 2003). The variables were checked for multicolinearity by calculating the variance inflation factors (VIF).…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%